YIA4 The Novel Alpha-V Beta-3 Integrin Positron Emission Tomography Radiotracer 18F-Fluciclatide is a Marker of Aortic Atherosclerosis Activity. (6th June 2015) - Jenkins, William; Vickers, Anna; Fletcher, Alison; Neale, Anoushka; Dweck, Marc; Lucatelli, Christophe; Newby, David
Abstract : Introduction: Intra-plaque angiogenesis and inflammation are key promoters of plaque vulnerability. Angiogenic endothelial cells and macrophages express the integrin αv β3 . The novel RGD-based radiotracer 18F-Fluciclatide has high affinity for αv β3 integrin and therefore may act as a surrogate marker of the unstable atherosclerotic plaque. Methods: Forty-six subjects with a mixture of ischaemic heart disease and aortic stenosis, including 9 healthy subjects underwent CT-coronary angiography (CTCA) and combined PET/CT imaging of the thorax 40 min after the administration of 226 ± 13 mBq 18F-fluciclatide. Regions of interest were drawn around the thoracic aorta using serial axial slices on fused PET/CT images. 18F-Fluciclatide uptake in these regions was normalised for blood-pool activity in the superior vena cava using tissue to background ratio [TBR]. Reproducibility of this technique was assessed on 10 image-sets by two observers. Quantification and analysis of descending thoracic aortic atheroma on CTCA was performed using plaque analysis software. Results: There was a close correlation between 18F-fluciclatide uptake and the extent of atherosclerosis within the aorta on CTCA, as measured by wall thickness (r = 0.62 [0.31–0.81], p= <0.001] and total plaque burden (r = 0.60 [0.27–0.80], p = 0.001). Furthermore, aortic 18F-fluciclatide uptake (expressed as mean TBRmax ) correlated with total aortic calcium score (AU) (r = 0.36 [0.05–0.60], p = 0.02) and was significantly greater in subjects with ischaemic heart disease (1.34 ± 0.03 vs 1.25 ± 0.03; p = 0.02) and hypercholesterolaemia (1.35 ± 0.03 vs 1.25 ± 0.03; p = 0.01). There were no significant age (r = 0.20(–0.12–0.47), p = 0.21) or sex related differences (1.34 ± 0.05 vs 1.29 ± 0.02, p = 0.24) and reproducibility analysis showed no fixed or proportional bias (0.07[–0.13–0.27]) with excellent intra-class correlation (0.98[0.92–1.0]). Conclusion: The quantification of αv β3 integrin expression within the aorta using 18F-fluciclatide is a highly reproducible marker of atherosclerotic burden. This supports further work in establishing its role in the assessment of the unstable plaque.